2001
DOI: 10.1046/j.1525-1594.2001.06863.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Damage Caused by the Centrifugal Pump: Laser‐Light Scattering Analysis of Aggregation Patterns

Abstract: Platelets are damaged by shear force during centrifugal pumping; however, the mechanism of this damage has not been fully investigated. A new laser-light scattering (LS) assay method enables quantification of real-time changes in the number of platelet aggregates of different sizes. Using this method, we assessed the kinetics of platelet damage caused by the centrifugal pump from the standpoint of platelet aggregation capacity. Conventional optical density (OD) and LS methods were used to measure platelet aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The platelet count allows an assessment to be made of blood damage (11). In fact, it is known that platelets can be damaged by shear stress in centrifugal pumps (12). Our finding on platelet count suggests that even though the flow in the new pump has a centrifugal component, the addition of the pulsatile component does not impair performance.…”
Section: Discussionmentioning
confidence: 70%
“…The platelet count allows an assessment to be made of blood damage (11). In fact, it is known that platelets can be damaged by shear stress in centrifugal pumps (12). Our finding on platelet count suggests that even though the flow in the new pump has a centrifugal component, the addition of the pulsatile component does not impair performance.…”
Section: Discussionmentioning
confidence: 70%
“…To the best of our knowledge, despite the abundance of studies that quantitatively assessed the effect of platelet activation (i.e., thrombus formation) in ECC components (Mellgren et al 1996;Tanaka et al 2001), there are no studies that quantitatively assessed the mechanical factors initiating platelet activation in ECC membrane oxygenators. Gartner et al (2000) demonstrated that low velocity regions qualitatively matched regions with a high incidence of thrombotic deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on BRDs for ECC focused on the experimental quantification of the effects of platelet activation, by measuring the dimension of platelet aggregates in centrifugal pumps (Tanaka et al 2001), computing the progression of thrombus growth in hemodialyzers and oxygenators (Goodman et al 2005) and comparing the formation of platelet microaggregates in centrifugal and roller pumps (Linneweber et al 2002). However, at present, there is a lack of mechanistic insight into the factors that determine platelet activation in these devices.…”
Section: Introductionmentioning
confidence: 99%
“…Shear stress and zones of stagnation and recirculation are associated with suboptimal fl ow which result in activation of red blood cells, white blood cells and platelets [8][9][10] . The damage is most prominent in a low-fl ow highresistance setting.…”
Section: Mecc Equipmentmentioning
confidence: 99%